(untitled) (Research, Society and Development, 2020)
This article aimed to report an experience of a group of mothers, in which the transgenerational aspects and their relationship with the Styles of exercise of motherhood were analyzed, as well as emphasizing the relevance of each pattern of caring toward their offspring infant development. This is a qualitative research carried out at the Laboratory of Practices in Psychology of a private University located in a city in the interior of Rio Grande do Sul. The group was formed by five caregivers of children aged six to eight years. The meetings followed structured sessions, based on cognitive-behavioral techniques and scheme therapy, and took place weekly for one hour, totaling six meetings. Semi-structured interviews with the families, a questionnaire of parental self-assessment and self-monitoring and a field diary produced by the researchers were used. It can be seen, from the intervention performed, that the mothers, for the most part, presented aspects of Authoritarian Style in care, establishing norms and limits without flexibility in parenting and with little regard for the children’s feelings. Concomitant to this, they reported a very strict parental education from their parents and with little explicit expression of affection. Another Parental Pattern presented by some mothers was the Neglect, characterized by having little time with their child and not establishing rules for him. In addition, participants with a childhood history of high level demand and little affection were found and now hope to provide their children with a different reality from the one they lived in, without clear limits and with great affection for their children, characterized by the Indulgent Style. It can be understood that Parenting Styles are directly related to affective transgenerationality of caregivers. The intervention enabled a space for exchanging affective experiences between caregivers and proved to be psychoeducative for the development of non-violent communication with the children.